2009
DOI: 10.33899/rjs.2009.39940
|View full text |Cite
|
Sign up to set email alerts
|

The Antioxidant Effects of Flavonoids and non Flavonoid Part Extracted from Ginger ( Zingiber Officinale) Roots.

Abstract: The extraction of Flavonoids from dried ginger ( Zingiber officinale Ros.) roots in addition of non-flavonoids parts (oils and defatted) were studied against H 2 O 2 induced oxidative stress in the serum of male rats for 15 day.Fifty male rats with age of 3-4 months and weight of 225-300 g were divided into 5 groups : group (1): control group received drinking tab water and ideal diet, group (2): received 0.5% H 2 O 2 in drinking tab water , group (3): received 0.5% H 2 O 2 and oral dose of 15 mg/ kg of BW. fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…When animals were treated with the nutraceutical beverage made from saffron extract, before or after giving them food contaminated with CCl 4 , groups G4 and G5 had total antioxidant capacities of 1.40 mol/ml and 1.38 mol/ml, respectively; a significant increase was observed compared to that in the group of animals fed with food contaminated with CCl 4 (G2), which only had 0.33 mol/ml. This result is consistent with the findings of Hamdoon et al [35], who observed an increase in glutathione level in male rats with hydrogen peroxide-induced oxidative stress after treatment with ginger extracts. The SEBB was able to raise the total antioxidant capacity because it contains the compounds crocin and safranal found in the saffron extract; these exogenous food antioxidants work to remove the constantly formed free radicals, protecting against the danger from these radicals as a line of defense against oxidative stress [36].…”
Section: Effects Of Nutraceutical Beverage On Total Antioxidantsupporting
confidence: 93%
“…When animals were treated with the nutraceutical beverage made from saffron extract, before or after giving them food contaminated with CCl 4 , groups G4 and G5 had total antioxidant capacities of 1.40 mol/ml and 1.38 mol/ml, respectively; a significant increase was observed compared to that in the group of animals fed with food contaminated with CCl 4 (G2), which only had 0.33 mol/ml. This result is consistent with the findings of Hamdoon et al [35], who observed an increase in glutathione level in male rats with hydrogen peroxide-induced oxidative stress after treatment with ginger extracts. The SEBB was able to raise the total antioxidant capacity because it contains the compounds crocin and safranal found in the saffron extract; these exogenous food antioxidants work to remove the constantly formed free radicals, protecting against the danger from these radicals as a line of defense against oxidative stress [36].…”
Section: Effects Of Nutraceutical Beverage On Total Antioxidantsupporting
confidence: 93%
“…This blood brings with it the absorbed materials in a concentrated form, where the liver enzymes work to remove the toxicity of some of the substances contained in the liver [16]. International Journal for Research in Applied Sciences and Biotechnology www.ijrasb.com Al-Khatib and his group [17] also explained that the hemorrhage in the tissue is the result of increased pressure inside the vessels, so there is a breakdown in the vessel wall and the exit of red blood cells. The cause of the dissolution of blood cells is the interactions between toxic compounds and glutathione, forming compounds that lead to the dissolution of blood cells.…”
Section: Discussionmentioning
confidence: 99%